RESEARCH AND DEVELOPMENT EXPENDITURES AND QUALITY OF LIFE IN EUROPEAN UNION COUNTRIES - Adam P. Balcerzak; Michał Bernard Pietrzak (Ekonomia i Prawo, 2015)
The improvement of people’s quality of life is currently considered as the main responsibility of every government. Due to the emergence of knowledge-based economy, it is commonly believed that investments in research and development (R&D) at a given level are a necessary condition for creating growth-based on innovations, thus supporting welfare in developed countries. In this context, the article is devoted to the analysis of influence of R&D expenditures on the quality of life in the European Union countries. As the main measure of the quality of life Human Development Index was utilized. Thus, the article can be considered as a contribution to the discussion on the potential of HDI index for measuring the quality of life in the case of narrow group of relatively developed countries. In the empirical part of the paper, panel data modeling fulfilling the postulates of dynamic estimation was used. The research was done for EU countries for the period 2004–2010. The empirical part takes into consideration the structural diversity between “old” and “new” members of the EU. First of all, the results can be treated as a voice confirming the usefulness of HDI as a measure of quality of life also from the perspective of narrow group of highly developed countries. Then, the research confirms the positive influence of R&D on European welfare only in the case of highly developed “old” member.